Rerooted and Reimagined: Dance, Palestinian Women, and the Reclamation of Urban Spaces - Hodel Ophir (Arts, 2022)
Manar Hasan employs the term “memoricide” to describe the systematic eradication of Palestinian society from modern memory, a process, she points out, that occurred not only through the destruction of its major cities, but also through the erasure from public consciousness the inhabitants of those cities, and specifically the Palestinian women who once played highly visible, integral roles within them. This paper enters into conversation with Hasan’s argument in its exploration of the work of Palestinian choreographer Shaden Abu Elasal, focusing on dances performed in urban spaces—locations from which she draws historical and creative inspiration to imbue her choreography with layers of meaning. I show how through her choreography, Abu Elasal reroots and uproots herself from the place in the very same acts of dance. She resurrects both the city and the women, revealing the obscured and retrieving the forgotten. I argue, then, that in staging dances in what Marc Augé terms “anthropological places” in Israel/Palestine, locations saturated with historical and conceptual significance, Abu Elasal both deepens her roots to the land, her land, and rises anew from it, freeing herself of its heavy shackles. Moreover, by reintroducing specifically Palestinian women dancers as elements of the “flesh and stone” of Israel/Palestine, spaces rife with histories of trauma, dominated by patriarchy and a Zionist ideology that privileges Jewishness and whiteness, Abu Elasal excavates a forgotten past, negotiates a restrictive present, and shapes a future for herself and her community. The paper brings together the ideas of anthropological space, which recognizes the identity of place as not merely physical but comprised of the breadth of human activity (symbolism, history, imagination, vision) that has taken and is taking place in it; and dance’s power to inspire a sense of losing oneself or transcending the existing, tangible world. In both ideas, consciousness and the material, stone and body, entwine and shape one another in the ongoing process of (re)forming identity and reclaiming history.